Benign regulation of short-chain fatty acids: the underlying mechanism of the beneficial effects of manual acupuncture on cognitive ability and the intestinal mucosal barrier in APP/PS1 mice - Ning Ding; Xin Hao; Yue Zhang; Yanxiang Zhang; Zhigang Li (Frontiers in Neuroscience)
BackgroundGut microbiota dysbiosis is closely related to the occurrence and progression of Alzheimer’s disease (AD). The destruction of the intestinal mucosal barrier caused by a decrease in short-chain fatty acids (SCFAs) plays a key role in gut microbiota dysbiosis-induced neuroinflammation in AD. Our previous research confirmed for the first time that manual acupuncture (MA) can benignly modulate gut microbiota dysbiosis, alleviating the destruction of the intestinal mucosal barrier. However, the regulatory effect of MA on SCFAs remains elusive, and the underlying mechanism by which MA improves intestinal mucosal barrier function requires elucidation.MethodsIn the APP/PS1 manual acupuncture (Am) group, MA was applied at Baihui (GV20), Yintang (GV29), and Zusanli (ST36). Probiotics were delivered to the APP/PS1 probiotic (Ap) group. Alterations in spatial learning and memory, intestinal barrier function, SCFAs in feces and serum, the expression of FFAR3 and NF-κB, and inflammatory cytokines were evaluated in each group.ResultsCompared with those in the C57BL/6 control (Cc) group, cognitive ability was significantly decreased, SCFAs and FFAR3 expression were obviously decreased, intestinal barrier integrity was drastically impaired, and the expression of NF-κB and the levels of intestinal IL-1β and TNF-α were increased in the APP/PS1 control (Ac) group. These changes were reversed by MA and probiotics.ConclusionMA can significantly reduce intestinal inflammation and alleviate destruction of the intestinal mucosal barrier in APP/PS1 mice. SCFAs/FFAR3/NF-κB may be important targets through which MA benignly regulates intestinal mucosal barrier function.